The Influence of Business Networking, Digital Capability, and Innovation on Entrepreneurial Success - Eka Sutisna; Franciscus Dwikotjo Sri Sumantyo; Enggar Widianingrum; Noorhani Dyani Lakssmi (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the influence of business networking, digital capability, and innovation on entrepreneurial success in the context of small and medium-sized enterprises (SMEs). In the rapidly evolving digital economy, entrepreneurs are required to leverage not only traditional resources but also strategic capabilities to achieve sustainable business performance. This research adopts a quantitative approach using a cross-sectional survey design. Data were collected from 200 SME owners and managers through structured questionnaires, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that business networking, digital capability, and innovation all have a positive and significant effect on entrepreneurial success. Among these variables, digital capability shows the strongest influence, highlighting the critical role of technology adoption and digital skills in enhancing business performance. Innovation also demonstrates a substantial contribution by enabling firms to create value, differentiate offerings, and respond to market changes. Meanwhile, business networking plays a significant role in providing access to resources, information, and opportunities that support business growth. Furthermore, the combined effect of these variables explains a substantial proportion of the variance in entrepreneurial success, indicating their complementary and synergistic relationships. This study contributes to the entrepreneurship literature by integrating business networking, digital capability, and innovation into a comprehensive research model. The findings provide practical implications for entrepreneurs to prioritize digital transformation, strengthen networking activities, and foster continuous innovation to achieve long-term success. Additionally, policymakers are encouraged to support entrepreneurial ecosystems by enhancing digital infrastructure, facilitating collaboration, and promoting innovation-driven initiatives.